Faktor Yang Berhubungan Dengan Kelelahan Kerja Pada Pegawai di Dinas Kesehatan Kabupaten Gorontalo Tahun 2024 - Suid, Nurafni (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The World Health Organization (WHO) predicts that the number 2 killer disease after heart disease is the feeling of severe fatigue. Data on work accidents in 2016, in Indonesia every day an average of 414 work accidents occurred, 27.8% were caused by high fatigue, approximately 9.5% or 39 people were disabled. The purpose of the study was to determine the factors associated with job fatigue in employees at the Gorontalo Regency Health Office in 2022. The research design used Analytical Observational with cross sectional study approach. The population in the study was 143 people, the sample in the study used total sampling of 143 people recorded at the Gorontalo Regency Health Office. The results of the study of 143 samples found that there was no significant relationship between tenure and length of service with a p value of 0.183, 0.346. Workload and work stress have a relationship with job fatigue in employees at the Gorontalo Regency Health Office in 2022 with a p value of 0.043 and 0.034. Suggestion this research It is expected that agencies should conduct routine health checks to minimise the risk of health problems caused by workload.